Paper-based origami flexible and foldable thermoelectric nanogenerator. (January 2017) - Rojas, Jhonathan P.; Conchouso, David; Arevalo, Arpys; Singh, Devendra; Foulds, Ian G.; Hussain, Muhammad M.
Abstract: Paper has been an essential material in our daily life since ancient times. Its affordability, accessibility, adaptability, workability and its easiness of usage makes it an attractive structural material to develop many kind of technologies such as flexible electronics, and energy storage and harvesting devices. Additionally, the scientific community has increased its interest on waste heat as an environmentally friendly energy source to support the increasing energy demand. Therefore, in this paper we described two affordable and flexible thermoelectric nanogenerators (TEGs) developed on paper substrates by the usage of simple micromachining and microfabrication techniques. Moreover, they exhibit mechanical stability and adaptability (through folding and cutting techniques) for a diverse set of scenarios where vertical or horizontal schemes can be conveniently used depending on the final application. The first TEG device, implemented on standard paper, generated a power of 0.5 nW (ΔT=50 K). By changing the substrate to a tearless and extra-smooth polyester paper, the TEG performance was optimized achieving less internal resistance and a greater power of ~80 nW (ΔT=75 K), at the cost of more rigidity in the substrate. This power represented over three times higher power production than the standard paper–based TEG with same dimensions, number of thermoelectric pairs and temperature difference. Another interesting aspect of paper based TEG is due to its foldability, one can control the temperature difference by unfolding (larger separation between hot and cold ends) and folding (smaller separation). Finally, one of the underlying objectives of this work is to spread the availability of essential technologies to the broad population by inclusion of everyday materials and simple processes. Graphical abstract: Highlights: Paper based thermoelectric nanogenerators (TEGs) are demonstrated. Nanoscale power is generated and can be enhanced by incorporating more thermopiles. Stiffer polyester paper based TEG shows better performance than standard paper. Foldable paper based TEG can be used to control the distance from hot to cold side.